2018
DOI: 10.3389/fphys.2018.01813
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota Modulation in Obesity-Related Non-alcoholic Fatty Liver Disease

Abstract: Obesity and associated comorbidities, including non-alcoholic fatty liver disease (NAFLD), are a major concern to public well-being worldwide due to their high prevalence among the population, and its tendency on the rise point to as important threats in the future. Therapeutic approaches for obesity-associated disorders have been circumscribed to lifestyle modifications and pharmacological therapies have demonstrated limited efficacy. Over the last few years, different studies have shown a significant role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 192 publications
2
75
0
Order By: Relevance
“…Due to the crucial role of gut microbiota and the lack of a gold standard treatment for NAFLD, strategies to modulate it, including the use of probiotics and prebiotics, emerge as potential therapeutic approaches. Recently, it has been discussed regarding the capacity of flavonoids to modulate gut microbiota composition, intestinal inflammation, and barrier integrity . Quercetin, flavonoid widely studied for its antioxidant and anti‐inflammatory properties, has demonstrated its ability to diminish lipid accumulation in the liver, ameliorate insulin resistance, and modulate lipogenic genes in animal models of metabolic syndrome and NAFLD .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the crucial role of gut microbiota and the lack of a gold standard treatment for NAFLD, strategies to modulate it, including the use of probiotics and prebiotics, emerge as potential therapeutic approaches. Recently, it has been discussed regarding the capacity of flavonoids to modulate gut microbiota composition, intestinal inflammation, and barrier integrity . Quercetin, flavonoid widely studied for its antioxidant and anti‐inflammatory properties, has demonstrated its ability to diminish lipid accumulation in the liver, ameliorate insulin resistance, and modulate lipogenic genes in animal models of metabolic syndrome and NAFLD .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been shown that gut microbiota transplantation from NAFLD‐prone donors can replicate the phenotype in germ‐free recipients . Underlying mechanisms are not completely understood yet, but they include dysbiosis‐induced deregulation of the intestinal barrier integrity and alterations in the metabolism of dietary and endogenous compounds, among others …”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota not only determines a differential extraction of nutrients and energy from the diet but also synthesizes a broad variety of metabolites that could modulate host metabolism, including ethanol, short‐chain fatty acids, secondary bile acids (BAs), and choline derivatives . BAs are synthetized from cholesterol in the liver and undergo metabolization by the gut microbiota in the intestine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenol-rich cocoa decreased the Firmicutes/ Bacteriodetes ratio and increased Faecalibacterium prausnitzii levels in pigs (59). The countering of intestinal microbiota dysbiosis in rats fed with an HFD and sucrose diet inhibited body weight gain, decreased serum insulin, reduced the Firmicutes/Bacteriodetes ratio, and restricted bacterium production associated with lifestyle-associated obesity (60,61). A relative increase in the abundance of bactericides in subjects drinking red wine polyphenols has also been reported (62).…”
Section: Polyphenols Alter the Gut Microbiota Compositionmentioning
confidence: 90%